Influence of epigallocatechin-3-gallate in promoting proliferation and osteogenic differentiation of human periodontal ligament cells - Jie Liu; Yi Lu; Jin Liu; Changxiong Jin; Yuchen Meng; Dandan Pei (BMC, 2019)
Abstract Background Epigallocatechin-3-gallate (EGCG) was recently proposed to have the potential to regulate bone metabolism, however, its influence on osteogenesis remains controversial. The present study aimed to investigate the effects of EGCG on the proliferation and osteogenesis of human periodontal ligament cells (hPDLCs). Methods Cells were cultured in osteogenic medium and treated with EGCG at various concentrations. Cell proliferation was analyzed using a CCK-8 assay and acridine orange (AO)/ethidium bromide (EB) staining. Flow cytometry was used to measure the intracellular reactive oxygen species (ROS) potential of hPDLCs. The expression levels of osteogenic marker genes and proteins in hPDLCs, including type I collagen (COL1), runt-related transcription factor 2 (RUNX2), osteopontin (OPN), and osterix (OSX), were determined by quantitative real-time polymerase chain reaction (qRT-PCR) and western blot analysis. In addition, alkaline phosphatase (ALP) activity was monitored both quantitatively and qualitatively. Extracellular matrix mineralization was further analyzed by alizarin red S staining. Results The results showed that EGCG concentrations from 6 to 10 μM increased the ROS level and inhibited the cell proliferation of hPDLCs. EGCG concentrations from 2 to 8 μM effectively increased extracellular matrix mineralization, in which 4 and 6 μM EGCG generated the most mineralizing nodules. The ALP activity and the mRNA and protein expression levels of the tested osteogenic markers were most strongly up-regulated by treatment with 4 and 6 μM EGCG. Conclusions The present study demonstrated that EGCG might promote the osteogenesis of hPDLCs in a dose-dependent manner, with concentrations of 4 and 6 μM EGCG showing the strongest osteogenic enhancement without cytotoxicity, indicating a promising role for EGCG in periodontal regeneration in patients with deficient alveolar bone in the future.